The Influence of the Problem Posing Learning Model on the Learning Outcomes of Class X Students of SMA Negeri 1 Bantaeng on Biodiversity Material - Nurnamira Rahman; Andi Faridah Arsal Andi Faridah Arsal; Andi Rahmat Saleh (PT. Ininnawa Paramacitra Edukasi, 2024)
This research is an experimental research with the Quasy Experiment Design research type which aims to determine the effect of the problem posing learning model on biology learning outcomes regarding biodiversity material in Class X SMA Negeri 1 Bantaeng. The independent variable of this research is the application of problem posing learning models and conventional learning models, while the dependent variable is student learning outcomes on biodiversity material. The population of this study was all students in class The research data was obtained by giving a test of learning outcomes on biodiversity material in the form of a pre-test and post-test. The data analysis technique was carried out using covariate analysis (Anakova). Based on the results of the analysis, P = 0.000 is smaller than α = 0.05. It can be concluded that the application of the problem posing learning model has a significant effect on the biology learning outcomes of class X SMA Negeri 1 Bantaeng on biodiversity material. Key words : problem posing, learning outcomes